Mémoires de Maximilien de Bethune duc de Sullyprincipal ministre de Henri-le-Grand, mis en ordre avec des remarques, par M.L.D.L.D.L. - Sully, Maximilien de Béthune, duc de, 1559-1641. (Tufts University. Tisch Library., 2015)
Volume 8 of 8.; Nouvelle édition, revue & corrigée.; 1 online resource (8 volumes); The imprint is false; possibly printed in Paris.; Imprint date on title page of volume 2 is misprinted: "MDCLXXVIII".; Includes indexes.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Binding: Tisch Library Special Collections copy: All volumes bound in tan mottled calf, green leather lettering piece to spines.; Indexed in: English short title catalogueT143312